2021
DOI: 10.4274/tjo.galenos.2020.23169
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Impact of the COVID-19 Pandemic on Ophthalmology Clinical Practice in Turkey

Abstract: Objectives: To investigate the effect of the novel coronavirus disease 2019 (COVID-19) pandemic on the clinical practice of ophthalmologists in our country. Materials and Methods: A questionnaire consisting of 22 questions was delivered to 250 ophthalmologists via e-mail and a smartphone messaging application. A total of 113 ophthalmologists completed the survey. The questions included the participants’ demographic data (age, years in practice, institution, and city), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
3
0
5
Order By: Relevance
“…The education of medical students and residents in many branches was also adversely affected by the pandemic (7)(8)(9). Ophthalmology residents and specialists are in the risky group for COVID-19 due to the long-term need for close contact with the patient and the risk of contamination from ocular surface (10). In this study, we conducted an online survey to investigate the effects of COVID-19 on ophthalmology residents compared to PreP.…”
Section: Discussionmentioning
confidence: 99%
“…The education of medical students and residents in many branches was also adversely affected by the pandemic (7)(8)(9). Ophthalmology residents and specialists are in the risky group for COVID-19 due to the long-term need for close contact with the patient and the risk of contamination from ocular surface (10). In this study, we conducted an online survey to investigate the effects of COVID-19 on ophthalmology residents compared to PreP.…”
Section: Discussionmentioning
confidence: 99%
“…An appointment system was adopted in clinics. In this context, several ophthalmological associations published guidelines for the treatment of patients with eye diseases (3,4). Individuals aged over 65 years in particular were unable to attend routine checkups for a long time because of fear of catching the infection in hospitals, restrictions on travel, and a lack of appointment availability stemming from limited numbers of patients being treated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from various countries have shown that the COVID-19 pandemic resulted in delays to intravitreal injection sessions and a decrease in the number of diabetic retinopathy and retinal vascular occlusions, which represent the most common causes of neovascular glaucoma. (2)(3)(4)(5)7). Delay of treatments in this way can result in a subsequent increase in the numbers of patients with neovascular glaucoma and in surgical procedures in elderly individuals.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 dünya genelinde hızla yayılan, sağlık sistemleri ve sağlık çalışanları üzerine olumsuz etkileri olan küresel bir salgına dönüşmüştür (1)(2)(3). Salgın, sağlık hizmet sunumu süreçlerinin önemli bir bileşeni olarak ön safhalarda yer alan uzmanlık öğrencilerinin yaşamında da önemli değişiklere yol açmıştır (4)(5)(6)(7). Küresel salgın ile mücadeleye yönelik araştırmalar sağlık profesyonellerinin sürece ilişkin algı ve deneyimlerinin önemine dikkat çekmektedir (1,8).…”
Section: Introductionunclassified
“…Amerika'da bulunan Mezuniyet Sonrası Tıp Eğitimi Akreditasyon Konseyi (ACGME) (24), Önceki salgın deneyimlerini de referans alarak (25,26) COVID-19 salgını sırasında eğitim ve öğretim faaliyetlerine yönelik öneriler geliştirmiştir. Araştırmalar, küresel salgınla mücadelede sağlık profesyonellerinin (1,12,15,16) ve tıpta uzmanlık öğrencilerinin (6,7,(9)(10)(11)…”
Section: Introductionunclassified